17β-estradiol binding to ERα promotes the progression of prolactinoma through estrogen-response element-induced CaBP-9k up-regulation. Issue 1 (14th January 2020) - Liu, Jun; Han, Hao; Lu, Wenpeng; Fan, Gaoyang
Abstract: 17β-estradiol (E2) is considered to be an important instigator of prolactinoma, and can positively regulate the expression of calbindin-D9k (CaBP-9k) which contains an estrogen responsive element (ERE) via estrogen receptors (ERs). However, the detailed mechanism of E2 in promoting CaBP-9k expression and their roles in prolactinoma progression remain unclear. Here, we aimed to characterize it. The luciferase gene reporter assay with luc-ERE transfection showed that E2 treatment significantly enhanced the transcriptional level of CaBP-9k, whereas CaBP-9k activity was reduced when GH3 and MMQ cells were treated with AZD9496, an antagonist of ERα. E2 treatment increased the protein expressions of CaBP-9k and ERα but not ERβ, whereas this effect was also abolished when cells were treated with AZD9496. Besides, immunoprecipitation (IP) and immunofluorescence assays demonstrated that CaBP-9k could directly interact with ERα not ERβ, and Chromatin IP (ChIP) assay showed that ERα could bind to ERE of the CaBP-9k promoter. Moreover, cell counting kit-8 (CCK-8) and flow cytometry assays showed that E2 treatment significantly enhanced cell viability and inhibited cell apoptosis, but these effects were all abolished when ERα was down-regulated by short hairpin RNA (shRNA) or inhibited by AZD9496, as well as CaBP-9K suppression in both GH3 and MMQ cell lines. Taken together, these findings indicated that E2 stimulation promoted prolactin cell proliferation and inhibited cell apoptosis through ERα-induced CaBP-9k up-regulation, which then accelerated the advanced progression of prolactinoma.